Effects of swimming towards mental health in collegiate male adults - Maisara Waheeda Adnan; Razalee Sedek; Sahilah Abd. Mutalib; Zalifah Mohd Kasim; Mohd Izhar Ariff Mohd Kashim; Fazilah Idris; Ashril Yusof (Penerbit Universiti Kebangsaan Malaysia, 2019)
Sports can be a non-pharmacological way to improve general human health. This study aimed at evaluating mental health among healthy male adults following swimming intervention as one of the recommended sports in Islam. A total of 28 adults aged 19-33 years old were randomly divided into two groups, swimming group (n=14) and control group (n=14). Two sets of questionnaires were employed, the Depression, Anxiety and Stress Scale (DASS) and the Profile of Mood State (POMS), which examined six domains i.e tension, depression, anger, fatigue, confusion, and vigour pre and post-intervention. The swimming group underwent an exercise program three times per week for eight weeks while the control group maintained their usual daily lifestyle. At baseline, there were significant differences were identified for all parameters measured in DASS and POMS excepts total mood disturbance and vigour domain between the two groups. While at post-intervention, there were significant differences between groups in anxiety and stress in DASS, as well as vigour domain in POMS (p< 0.05). After eight weeks of exercise, swimming group showed a significant reduction in all outcomes measured compared to the control group (p< 0.05). This study shows that eight weeks of swimming can exert positive effects on mental health in healthy male collegiate adults.